2019
DOI: 10.1038/s41467-019-09624-w
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the role of H3K27 acetylation and methylation in PRC2 mediated control of cellular identity

Abstract: The Polycomb repressive complexes PRC1 and PRC2 act non-redundantly at target genes to maintain transcriptional programs and ensure cellular identity. PRC2 methylates lysine 27 on histone H3 (H3K27me), while PRC1 mono-ubiquitinates histone H2A at lysine 119 (H2Aub1). Here we present engineered mouse embryonic stem cells (ESCs) targeting the PRC2 subunits EZH1 and EZH2 to discriminate between contributions of distinct H3K27 methylation states and the presence of PRC2/1 at chromatin. We generate catalytically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
192
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(222 citation statements)
references
References 79 publications
29
192
0
1
Order By: Relevance
“…On the other hand, whether H3K27ac functionally determinates enhancer activity is less clear because it is difficult to selectively target H3K27ac at enhancers. Nevertheless, it has been reported that H3K27ac plays an active role in cell identity control [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, whether H3K27ac functionally determinates enhancer activity is less clear because it is difficult to selectively target H3K27ac at enhancers. Nevertheless, it has been reported that H3K27ac plays an active role in cell identity control [7].…”
Section: Introductionmentioning
confidence: 99%
“…The PRC1 core is formed by the E3 ligases RING1A or RING1B that, by interacting with the products of one of the six Pcgf paralogue genes (PCGF1-6), catalyse the mono-ubiquitination of Histone H2A at Lysine 119 (H2AK119ub1) (Blackledge et al, 2014;Gao et al, 2012;Wang et al, 2004). The PRC2 core is composed by two mutually exclusive methyltransferases EZH1 and EZH2 that, by associating to the scaffold proteins SUZ12 and EED, catalyse mono-, diand tri-methylation of Histone H3 Lysine 27 (H3K27me1, me2 and me3) (Ferrari et al, 2014;Lavarone et al, 2019;Margueron et al, 2008;Shen et al, 2008). Both H2AK119ub1 and H3K27me3 are specifically enriched at repressed CpGi containing promoters and their loss correlates with increased transcriptional activity of target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Here we performed ChIPseq directly using rat carotid arteries that underwent angioplasty injury-induced IH. We observed a prominent injured-vs-uninjured genome-wide upsurge of H3K27me3, a repression mark 20 . This was, at first sight, counterintuitive since conventional views regard transcriptional activation as the prevailing event following injury in the IH model.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, BRD4 as an acetylation reader and EZH2 as a methylation writer are seemingly unrelated; their relationship has been overlooked 19 , especially in vascular pathogenesis. However, it is important to explore a functional connection between BRD4 and EZH2, both cell identity/state determinants 20 and targets of active clinical trials 14 .…”
Section: Introductionmentioning
confidence: 99%